Draft Annual Plan for 2001-2002 Volume-I Andaman and Nicobar Administration - Planning Commission (Planning Commission, 2001)
Rice cultivation and its importance in these Islands cropping system has no room to doubt about. The agriculture in these Islands is more recent and out of the total area of flat land available, paddy shares 12,000 ha. alone and there exists a little scope for further expansion of area. This available 12,000 ha. is utilised for cultivation of paddy, pulses, oilseeds, vegetable etc.
Andaman and Nicobar Administration, Planning Department